(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Chorniy M. Preparing future teachers to the formation of interpersonal relationships in a group of students as part of the mastery of professional competencies. This article presents an analysis of peculiarities of the future teacher training to the formation of interpersonal relations in the teenage pupil group in terms of competence approach.